2017
DOI: 10.1002/pssb.201700469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Finite Size on the Electrocaloric Response in PbTiO3 Ceramics Near Room Temperature Using Landau Theory

Abstract: We investigate the influence of grain size on the electrocaloric properties of ferroelectric systems using Landau theory. We study how the phase transformation temperature and electrocaloric property can be tuned by changing the grain size close to the critical size. Our results show that the electrocaloric coefficient at room temperature can be greatly enhanced by controlling the grain size. In particular, we calculate the adiabatic temperature change, ΔT to be %2 K with an electric field difference ΔE ¼ 50 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…found that when the grain size of BTO core–shell ceramics decreased to a critical size of 20 nm, the internal tetragonal core turn to cubic phase. Liu et al 94 . displayed that when the grain size of PTO ceramics was reduced to a critical size of 8.8 nm, its spontaneous polarization was suppressed to zero near RT.…”
Section: Intrinsic Influence Factors Of Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…found that when the grain size of BTO core–shell ceramics decreased to a critical size of 20 nm, the internal tetragonal core turn to cubic phase. Liu et al 94 . displayed that when the grain size of PTO ceramics was reduced to a critical size of 8.8 nm, its spontaneous polarization was suppressed to zero near RT.…”
Section: Intrinsic Influence Factors Of Materialsmentioning
confidence: 99%
“…Fang et al 97 found that when the grain size of BTO core-shell ceramics decreased to a critical size of 20 nm, the internal tetragonal core turn to cubic phase. Liu et al 94 displayed that when the grain size of PTO ceramics was reduced to a critical size of 8.8 nm, its spontaneous polarization was suppressed to zero near RT. Dai et al 100 also found that, at RT, BTO nanoshells with cylindrical cores exhibit an EC coefficient peak with a size-driven phase transition near the critical nanoshell thickness.…”
Section: Grain Sizementioning
confidence: 99%
See 1 more Smart Citation
“…This macroscopic thermodynamic approach is widely applied in the experiments of measuring the ECE without furnishing any microscopic properties of the materials studied. The second approach is the Landau phenomenological approach, which incorporates the correction of Curie temperature by crystal size and creates a quantitative connection between macroscopic material properties and the ECE. However, the Landau approach precludes the investigation of micromechanisms. Pirc et al introduced a microscopic dipole model to estimate the upper bound value of ECE temperature, but this model is not directly applicable to systems under finite values of E or for understanding material responses to changing external electric fields.…”
mentioning
confidence: 99%